Variation in maltose in sweet wort from barley malt and rice adjuncts with differences in amylose structure. Issue 1 (26th December 2018) - Fox, G.; Yu, W.; Nischwitz, R.; Harasymow, S.
Abstract : Starch from malt and solid adjuncts provides the majority of fermentable sugars for fermentation. However, there is no current data on the variation in starch structure (particularly long chained amylose) and its impact on the final wort composition of fermentable sugars, specifically maltose. This is the first study to report variation in amylose structure from barley malt and rice used as an adjunct and how this impacts the production of maltose. We compared four commercial malts with two rice adjuncts mashes, in solid and liquid additions, with an all‐malt mash used as a control. All combinations of malt and rice adjuncts were tested under two grist‐to‐liquor (G:L) ratios (1:3 and 1:4) in a 65°C ramped mash. After mashing, the wort original gravity and maltose concentration were measured. The commercial malts had different malt quality but very similar gelatinisation temperatures ( 65°C). The malts varied in starch and amylose contents but had only minor variations in average amylose chain lengths. The two rice adjuncts also had similar average amylose chains lengths, but quite different amylose contents, and hence different gelatinisation temperatures. The results showed that liquid adjunct mashes had higher original gravity and maltose concentration for both G:L ratios. However, there was no consistent result in original gravity or maltose between G:L ratio or adjunct type, suggesting interactions between each malt and rice adjunct. Knowing amylose chain length could improve understanding of the potential maltose levels of the sweet wort prior to fermentation. © 2018 The Institute of Brewing & Distilling